Disonansi Makna Cantik Remaja di Kota Waingapu - Rambu Naha (Universitas Merdeka Malang, 2021)
Beauty is defined through the process of social interaction and the use of symbols. Social interaction could define distinct meaning about reality. Youths in Waingapu, East Timor, interact within cultural context that is filled with values passed from generation to generation, and that includes how to define the meaning of beauty. As youths who live in an era of fast development of conventional and social media, youths are interacting with both cultural and social – constructed by media – values. This research aims to describe how the meaning of beauty is defined in Waingapu. To accomplish its objective, the research uses descriptive qualitative approach by conducting interview with ten youths from Waingapu. The result shows that youths in Waingapu define meaning of beauty from two opposite sides. They are facing a dissonance in which two values are going to two different directions. They however realize that the meaning of beauty is mainly defined by character – in accordance with the culture of people in Sumba – but they are unable to set aside the ideas that are constructed by media on the definition of beauty. Keywords: Meaning of Beauty, Symbolic Interactionism, Youths in Waingapu DOI: https://doi.org/10.26905/nomosleca.v7i1.5485